Effect of intercropping maize and cassava with upland NERICA rice varieties on stemborer attack in southwest Nigeria - Nwilene, F.E.; Onasanya, A.; Togola, A.; Oyetunji, O.; Semon, M.; Tamo, Manuele; Bright, E.O.; Ofodile, S. (Science Alert, 2011)
Rice and maize intercrop is a common feature of traditional upland rice cultivation in Nigeria. Stemborer larvae cause significant yield loss in rice. The study aimed at identifying stemborer resistant status of upland NERICA rice varieties and evaluating the effectiveness of maize as a trap crop to protect upland NERICA rice varieties against stemborers. The resistance status of 7 NERICA rice and 2 other rice varieties to stemborer was evaluated in 2006 and 2007 under natural infestation maize and cassava intercropping systems in the humid forest zone of Nigeria. In 2006 study, NERICA1, NERICA2 and NERICA5 together with the resistant check LAC23 were classified as stemborer resistant (SBR) and NERICA3, NERICA4, NERICA6 and NERICA7 together with susceptible check OS6 were classified as stemborer susceptible (SBS). The SBR varieties (NERICA1 and NERICA2) from the 2006 study intercropped with maize and cassava in 2007 revealed the effectiveness of maize as a trap crop and cassava as a refuge for generalist predators against stemborer damage on upland rice. Maize appeared an effective trap crop for rice stemborers because there was a marked and significant reduction in the stemborer attack on rice in the NERICA rice/maize intercrops (GrB cluster) as compared to the NERICA rice monocrops (GrA cluster) and NERICA rice/cassava intercrops (GrA cluster). Maliarpha separatella Ragonot was the predominant stemborer species on rice followed by Sesamia calamistis Hampson. It was concluded that NERICA1 and NERICA2 could be recommended to farmers in stemborer prone areas and that maize was a suitable trap crop for managing rice stemborers.